67-2x+6=5x-2

Simple and best practice solution for 67-2x+6=5x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 67-2x+6=5x-2 equation:


Simplifying
67 + -2x + 6 = 5x + -2

Reorder the terms:
67 + 6 + -2x = 5x + -2

Combine like terms: 67 + 6 = 73
73 + -2x = 5x + -2

Reorder the terms:
73 + -2x = -2 + 5x

Solving
73 + -2x = -2 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
73 + -2x + -5x = -2 + 5x + -5x

Combine like terms: -2x + -5x = -7x
73 + -7x = -2 + 5x + -5x

Combine like terms: 5x + -5x = 0
73 + -7x = -2 + 0
73 + -7x = -2

Add '-73' to each side of the equation.
73 + -73 + -7x = -2 + -73

Combine like terms: 73 + -73 = 0
0 + -7x = -2 + -73
-7x = -2 + -73

Combine like terms: -2 + -73 = -75
-7x = -75

Divide each side by '-7'.
x = 10.71428571

Simplifying
x = 10.71428571

See similar equations:

| 10=-2x+22 | | 3(x-45)+2x=540 | | -9+4r=-3-6 | | 4x+2=4x+6 | | 11x^2+2x+24=0 | | -10w+3=52 | | 67-(2x+6)=5x-2 | | 8(7y+6z)-48z= | | 15=-3n | | 9x+84=28x | | 12g=-108 | | -4x-14=6-2x | | 3x-2(3+x)=9 | | 7(x-5)=-7(x+5) | | 10a^4b-25a^3b+15ab=0 | | 0.5(4a+10B)=C | | (x^2+3)+(4+2x)=15 | | -6=5t+4 | | p/7=21 | | 6x+4=20x+7 | | 11x-8=12+x | | -16m=48 | | 2p^2+3p^2-8p^3-6p^3= | | 6x+4-1=20x+6 | | 3x-2(7-2y)=10 | | 4x-3=2x-5 | | -13+6x-7+3x=1+x | | 6x+4-1=20x+1 | | 2p^3+3p^2-8p^3-6p^3= | | y/(-8)=9 | | 2x+7=-7x+88 | | 31=-16m |

Equations solver categories